Ovarian pregnancy: a case-report - Maia,Ana Filipa (2024)
Abstract Ovarian pregnancy is a rare form of ectopic pregnancy. Only 3% of all ectopic pregnancies are primarily located in the ovary, having a global incidence of 1/2100 to 1/7000 pregnancies. Risk factors include prior ectopic pregnancy, pelvic infections, infertility, tubal surgery and intrauterine device placement. Clinical presentation is undistinguishable from other forms of ectopic pregnancy and ultrasonographic diagnosis is unspecific. Although most end up in miscarriage, approach is similar to other ectopic pregnancies, either with medical or surgical treatment. The authors present a case of ovarian pregnancy in a primiparous healthy woman, diagnosed during surgery and confirmed with histological examination.